Next-generation sequencing of cancer consensus genes in lymphoma - Hüllein, Jennifer; Jethwa, Alexander; Stolz, Tatjana; Blume, Carolin; Sellner, Leopold; Sill, Martin; Langer, Christian; Jauch, Anna; Paruzynski, Anna; Kalle, Christof von; Schmidt, Manfred; Glimm, Hanno; et al. (Leukemia and lymphoma, 2013)
Sensitive identification of mutations in genes related to the pathogenesis of cancer is a prerequisite for risk-stratified therapies. Next-generation sequencing (NGS) in lymphoma has revealed genetic heterogeneity which makes clinical translation challenging. We established a 454-based targeted resequencing platform for robust high-throughput sequencing from limited material of patients with lymphoma. Hotspot mutations in the most frequently mutated cancer consensus genes were amplified in a two-step multiplex-polymerase chain reation (PCR) which was optimized for homogeneous coverage of all regions of interest. We show that targeted resequencing based on NGS technologies allows highly sensitive detection of mutations and assessment of clone size. The application of this or similar techniques will help the development of genotype-specific treatment approaches in lymphoma.